2010
DOI: 10.1016/j.jvs.2009.07.111
|View full text |Cite
|
Sign up to set email alerts
|

Primary leiomyosarcoma of the inferior vena cava: Reports of infrarenal and suprahepatic caval involvement

Abstract: We report two cases of primary inferior vena cava (IVC) leiomyosarcoma. The first patient was a 60-year-old female who presented with abdominal pain. The patient was initially diagnosed with a retroperitoneal sarcoma that may have involved the right renal vessels and the IVC. The Vascular Surgery Service was consulted intra-operatively when it became evident that the IVC was primarily involved. The patient was treated with total en-bloc excision of the infrarenal IVC tumor with concomitant interposition polyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 17 publications
(15 reference statements)
0
18
0
Order By: Relevance
“…Mingoli et al [3] described the following three regions within the IVC for tumor involvement: (i) the lower segment (infrarenal) (37%), (ii) the middle segment (from the hepatic veins to the renal veins) (44%), and (iii) the upper segment (from the right atrium to the hepatic veins) (20%). [3,9,15] Similarly, according to Kulaylat, [5] primary tumors of the IVC occur in three different segments: segment I (below the inflow of the renal veins), segment II (from the inflow of the renal veins to the inflow of the hepatic veins, excluded), and segment III (from the inflow of the liver veins up to the right atrium). The authors found that segment II was more often involved (46%) than segment I (38%) or segment III (16%).…”
Section: Grading and Classificationmentioning
confidence: 97%
See 4 more Smart Citations
“…Mingoli et al [3] described the following three regions within the IVC for tumor involvement: (i) the lower segment (infrarenal) (37%), (ii) the middle segment (from the hepatic veins to the renal veins) (44%), and (iii) the upper segment (from the right atrium to the hepatic veins) (20%). [3,9,15] Similarly, according to Kulaylat, [5] primary tumors of the IVC occur in three different segments: segment I (below the inflow of the renal veins), segment II (from the inflow of the renal veins to the inflow of the hepatic veins, excluded), and segment III (from the inflow of the liver veins up to the right atrium). The authors found that segment II was more often involved (46%) than segment I (38%) or segment III (16%).…”
Section: Grading and Classificationmentioning
confidence: 97%
“…The use of cavography is also important in cases of IVC occlusion in order to demonstrate collateral flow and plan the appropriate surgical strategy. [2,10] Confirmation of the diagnosis is done via a histopathological examination after intravenous, fluoroscopic CT, a duplex-guided biopsy, or usually after surgical resection, [9] as was performed in our case.…”
Section: Diagnosismentioning
confidence: 99%
See 3 more Smart Citations